Affirmation of Women’s Representation in the 2024 Election: Enforcement Through Judicial Power Institution - Dungga Weny; Kasim Nur M.; Tome Abdul Hamid; Rahim Erman I.; Arief Supriyadi A. (SHS Web of Conferences)
This article examines the extent to which efforts to enforce affirmation of women’s representation in the implementation of elections in Indonesia and a comparative study between Indonesia and South Korea is also conducted. This issue will be examined normatively. The results of the study show that the decline in affirmation of women’s representation occurred after the issuance of General Election Commission Regulation Number 10 of 2023 which changed the method of calculating female legislative candidates to rounding down as regulated Article 8 paragraph (2) even though affirmation of women’s representation in Indonesia shows positive developments such as in South Korea. This issue was resolved through Supreme Court Decision No. 24 P/HUM/2023 which revokes the substance Article 8 of the General Election Commission Regulation Number 10 of 2023 which is also supplemented by the Constitutional Court Decision No. 125-01-08-29/PHPU.DPR-DPRD-XXII/2024 which revokes the results of the General Election in the electoral district of Gorontalo 6 because it does not meet the number of women’s representation and at the same time orders the General Election Commission to hold a re-election, indicating an effort to uphold the affirmation of women’s representation in the implementation of general elections in Indonesia through the judicial power institution.